Two temperate sub-Neptunes transiting the star EPIC 212737443. Issue 1 (14th June 2019) - Herath, Mahesh; Hinse, Tobias C; Livingston, John H; Hernández, Jesús; Evans, Daniel F; Wells, Robert; Gunesekera, Saraj; Tregloan-Reed, Jeremy; Rabus, Markus; Skottfelt, Jesper; Dominik, Martin; Jørgensen, Uffe G; et al.
ABSTRACT: We report the validation of a new planetary system around the K3 star EPIC 212737443 using a combination of K 2 photometry, follow-up high-resolution imaging and spectroscopy. The system consists of two sub-Neptune sized transiting planets with radii of 2.6 R ⊕ and 2.7 R ⊕, with orbital periods of 13.6 and 65.5 d, equilibrium temperatures of 536 and 316 K, respectively. In the context of validated K 2 systems, the outer planet has the longest precisely measured orbital period, as well as the lowest equilibrium temperature for a planet orbiting a star of spectral type earlier than M. The two planets in this system have a mutual Hill radius of Δ R H = 36, larger than most other known transiting multiplanet systems, suggesting the existence of another (possibly non-transiting) planet, or that the system is not maximally packed.